Meta-analysis of plant growth-promoting rhizobacteria interaction with host plants: implications for drought stress response gene expression - Ferrante, Roberta; Campagni, Chiara; Vettori, Cristina; Checcucci, Alice; Garosi, Cesare; Paffetti, Donatella (Frontiers in Plant Science, 2024)
Introduction The molecular and physiological mechanisms activated in plants during drought stress tolerance are regulated by several key genes with both metabolic and regulatory roles. Studies focusing on crop gene expression following plant growth-promoting rhizobacteria (PGPR) inoculation may help understand which bioinoculant is closely related to the induction of abiotic stress responses. Methods Here, we performed a meta-analysis following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to summarise information regarding plant-PGPR interactions, focusing on the regulation of nine genes involved in plant drought stress response. The literature research yielded 3,338 reports, of which only 41 were included in the meta-analysis based on the chosen inclusion criteria. The meta-analysis was performed on four genes (ACO, APX, ACS and DREB2); the other five genes (ERD15, MYB, MYC, acdS, WRKY) had an insufficient number of eligible articles. Results Forest plots obtained through each meta-analysis showed that the overexpression of ACO, APX, ACS and DREB2 genes was not statistically significant. Unlike the other genes, DREB2 showed statistically significant results in both the presence and absence of PGPR. Considering I2>75 %, the results showed a high heterogeneity among the studies included, and the cause for this was examined using subgroup analysis. Moreover, the funnel plot and Egger’s test showed that the analyses were affected by strong publication bias. Discussion This study argues that the presence of PGPR may not significantly influence the expression of drought stress response-related crop genes. This finding may be due to high heterogeneity, lack of data on the genes examined, and significant publication bias.